2022
DOI: 10.1007/s00253-022-12041-7
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative potential of Lactobacillus sp. in ameliorating D-galactose-induced aging

Abstract: Aging is a progressive, unalterable physiological degradation process of living organisms, which leads to deterioration of biological function and eventually to senescence. The most prevalent factor responsible for aging is the accumulation of damages resulting from oxidative stress and dysbiosis. D-galactose-induced aging has become a hot topic, and extensive research is being conducted in this area. Published literature has reported that the continuous administration of D-galactose leads to the deterioration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 82 publications
(125 reference statements)
0
8
0
Order By: Relevance
“…2(e)) and NO (Fig. 2(f)) increased in the MC group compared with the NC group, showing oxidative damage caused by d ‐galactose 15 . In the three intervention groups, levels of T‐SOD and CAT significantly increased, and serum levels of MDA and NO significantly decreased.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…2(e)) and NO (Fig. 2(f)) increased in the MC group compared with the NC group, showing oxidative damage caused by d ‐galactose 15 . In the three intervention groups, levels of T‐SOD and CAT significantly increased, and serum levels of MDA and NO significantly decreased.…”
Section: Resultsmentioning
confidence: 86%
“…2 compared with the NC group, showing oxidative damage caused by D-galactose. 15 In the three intervention groups, levels of T-SOD and CAT significantly increased, and serum levels of MDA and NO significantly decreased. Oxidant stress caused by overproduction of reactive oxygen species and/or deficiency of antioxidant defenses can induce cellular senescence.…”
Section: Effect Of the Consumption Of De-branched Starch-fatty Acid C...mentioning
confidence: 87%
“…In a short period of time, most of the probe was concentrated in the heart, kidney, and liver regions, and only a minority reached the lesion site. , As shown in Figure b,c, the fluorescence changes of whole body imaging within 5–90 min in specific channels of mice were detected by animal imager to indicate the activity of β-gal. In the green channel (480–530 nm), with the increase of incubation time, the control group had no obvious enhancement, while the brain and muscle parts of the senescence group 1 and 2 had obvious fluorescence enhancement, which proved that the senescence parts of the mice had highly active β-gal. While in the red channel (580–630 nm), most of the probe was retained in the heart, kidney, and liver regions; therefore, the fluorescence from the red channel in the corresponding areas was clearly visible. Figure d–f shows the fluorescence quantitative values near the right lower limb of the mice (selected areas in Figure b–c) from the green channel and red channel of the control group and experimental groups 1 ( d -galactose) and 2 (HU).…”
Section: Resultsmentioning
confidence: 98%
“…The experiment constructed a d -galactose-induced senescence mouse model widely used in biological research. Studies have shown that long-term injection and absorption of d -galactose can cause symptoms similar to natural aging. d -Galactose induces senescence by reducing respiratory chain enzyme activity and ATP synthesis, leading to mitochondrial dysfunction and increasing ROS production . HU is also considered to be a drug that causes senescence and exerts an antimetabolic compound effect by inhibiting ribonucleotide reductase .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation